THE EFFECT OF KNOWLEDGE MANAGEMENT AND INNOVATION ON UMKM PERFORMANCE MEDIATED BY ORGANIZATIONAL SUPPORT AT THE TRADE, COOPERATIVE AND UMKM SERVICE OF EAST BARITO REGENCY - Bertha Novianty; Noor Ritawaty2 (Sean Institute, 2022)
This study aims to find out and prove whether Knowledge Management and Innovation have an effect on MSME performance mediated by organizational support at the Trade, Cooperative and UKM Office of East Barito Regency. The population of this study were 4,810 MSME actors and the sample size was calculated using the Slovin formula, totaling 98 MSME actors using the Porpusive sampling technique. The research instrument was a questionnaire distributed to a sample of MSME actors in East Barito Regency. The data analysis technique used for path analysis uses the Smart PLS Version 3.2.0 application. The results of the study stated that knowledge management had a positive and significant effect on organizational support, innovation had a positive and significant effect on organizational support, knowledge management had a positive and significant effect on MSME performance, innovation had a positive and significant effect on MSME performance, organizational support had a positive and significant effect on MSMEs performance, Organizational Support mediates the effect of knowledge management on MSME Performance, Organizational Support mediates the influence of Innovation on MSME performance